Impact of a Nurse-Directed Wellness Program on Psychological Well-Being and Functional Capacity Among the Elderly - Ms. Palak Patel,; Dr. Ravindra H.N, (The Bioscan, 2025)
As aging populations increase globally, maintaining both physical independence and psychological well-being becomes essential for healthy aging. Anxiety and depression are common but under-recognized issues in older adults, often coexisting with declining functional capacity. This study evaluates the effectiveness of a structured, nurse-led wellness programme in improving functional and mental health outcomes among elderly individuals in Vadodara. Objectives: To assess the impact of a nurse-directed wellness programme on functional capacity, depressive symptoms, and anxiety levels, and to explore their association with key socio- demographic variables.